Worldwide review with meta-analysis of women's awareness about breast cancer. Issue 7 (July 2022) - Wang, Yong-Jiu; Wang, Fei; Yu, Li-Xiang; Xiang, Yu-Juan; Zhou, Fei; Huang, Shu-Ya; Zheng, Chao; Fu, Qin-Ye; Li, Liang; Gao, De-Zong; Zhang, Qiang; Ma, Zhong-Bing; et al.
Highlights: Average breast cancer awareness level is still low in developing countries. Women should be educated to prevent breast cancer effectively. This is the largest-scale systematic analysis on breast cancer awareness. Cumulative and subgroup analysis were first used in this type of review. Abstract: Objective: To summarize the awareness levels of breast cancer (BC) worldwide and investigate factors associated with BC awareness to determine differences in awareness between China and other countries. Methods: This systematic review followed the PRISMA guidelines and included 92 articles up to July, 2021. We calculated percentages for BC awareness levels and conducted subgroup analysis and cumulative meta-analysis. Results: A total 84% (95% confidence interval [95%CI]: 78–90%) of women knew about BC; however, only 51% (95%CI: 37–66%) and 40% (95%CI: 24–56%) of women were aware of BC symptoms and BC risk factors, respectively. The most commonly known BC symptom was breast lump (71%, 95%CI: 62–80%), and BC family history was the most well-known BC risk factor (61%, 95%CI: 54–69%). Subgroup analysis showed lower awareness levels among Chinese and Asian women than women from other countries. Cumulative meta-analysis showed no obvious progress in BC awareness levels over time. We investigated 15 awareness-related factors, the most frequent of which were education level (61.8%), occupation (29.4%), and age (26.5%). Conclusion: BC awareness levels remain low. Improving BC awareness is critical, especially in developing countries. Practice Implications: Effective education programs are urgently needed to improve women's BC awareness.